2019
DOI: 10.1021/jasms.9b00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Water in a Linear Quadrupole Ion Trap on the Protonation Sites of 4-Aminobenzoic Acid

Abstract: In solution, the most basic site in 4-aminobenzoic acid is the amino nitrogen, while the carboxylic acid oxygen is the most basic site in the gas phase. However, the protonation site in the gas phase has been demonstrated to depend on the ionization solvents when ionized using positive ion mode electrospray ionization (ESI). In many of these studies, collision-activated dissociation (CAD) was used to differentiate the protomers. To explore the influence of different CAD conditions on the manifested protonation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…As Seo et al have suggested, the proton relocation is inhibited by acetonitrile. We propose that acetonitrile forms a strong complex with N -protonated PABA and thereby prevents the transformation of the N -protomer to the gas-phase favored O -protomer . In fact, we stipulated previously that the kinetic trapping , of the energetically less favored N -protomer is a gas-phase phenomenon .…”
Section: Resultsmentioning
confidence: 97%
“…As Seo et al have suggested, the proton relocation is inhibited by acetonitrile. We propose that acetonitrile forms a strong complex with N -protonated PABA and thereby prevents the transformation of the N -protomer to the gas-phase favored O -protomer . In fact, we stipulated previously that the kinetic trapping , of the energetically less favored N -protomer is a gas-phase phenomenon .…”
Section: Resultsmentioning
confidence: 97%
“…3,4 In general, the protonation site of an organic molecule highly depends on the surrounding solvent. 6–22 This solvent-dependent behavior is particularly prominent for molecules with multiple basic sites. For example, benzocaine (BC), which has both carbonyl and amino groups, is most stable in its NH 2 -protonated form (N-protomer, H + BC( N )) in polar solvents, whereas the CO-protonated form (O-protomer, H + BC( O )) is most stable in the gas phase (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This solvent-dependent protonation-site switching is not only found in BC but prevails in other (bio-)organic molecules. 16–33 Much effort has been devoted to microsolvated clusters, in which an ion is solvated by a few to several hundreds of molecules, 14,34–36 because the degree of solvation can be tuned by controlling the type and numbers of solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the possible influence of the concentration of 4-aminobenzoic acid on the manifested protonation sites after APCI in a linear quadrupole ion trap (LQIT) mass spectrometer when using two different solvent systems. While CAD has been commonly used for the structural elucidation of the protomers of 4-aminobenzoic acid, , this method cannot be used to differentiate the protomers in LQIT mass spectrometers because residual water present in the ion trap can change the protonation site . Thus, gas-phase ion–molecule reactions between trimethoxymethylsilane (TMMS) and protonated 4-aminobenzoic acid were employed instead.…”
Section: Introductionmentioning
confidence: 99%
“…While CAD has been commonly used for the structural elucidation of the protomers of 4-aminobenzoic acid, 15,26 this method cannot be used to differentiate the protomers in LQIT mass spectrometers because residual water present in the ion trap can change the protonation site. 27 Thus, gas-phase ion− molecule reactions between trimethoxymethylsilane (TMMS) and protonated 4-aminobenzoic acid were employed instead. TMMS has been reported to react with protonated hydroxylamines and protonated carboxylic acids to generate different products: a stable adduct is generated for protonated hydroxylamines while an adduct that has lost a methanol molecule is observed for protonated aliphatic and aromatic carboxylic acids.…”
Section: ■ Introductionmentioning
confidence: 99%